RANCANGAN RANGKAIAN SIMULASI LUXMETER DENGAN MENGGUNAKAN SENSOR LIGHT DEPENDENT RESISTOR (LDR) BERBASIS MIKROKONTROLER AT89S52 DENGAN PROGRAM PROTEUS 7.0 - Widiantara, I Kadek; Supardi, I Wayan; Wendri, Nyoman (BULETIN FISIKA, 2016)
It has been designed a series of simulations using sensors Luxmeter Light Dependent Resistor (LDR) based Microcontroller AT89S52 with proteus 7.0 program that has a variety of functions and can be used to assist the people work. One of its functions can be applied as a measure of light intensity. Program into the controller of the system Lux Meter work and most of the performance is determined by a given program. Speed performance of a device based mikrokontroler also very dependent on the value of the frequency of the crystal oscillator is used.